Identifying Energy-Use Behavior and Energy-Use Profiles of Hotel Guests - Hevar Palani (Applied Sciences, 2021)
There are about 47,000 hotels in the United States that spend an average of $2200 per room on energy annually. Studies found that hotel guests’ energy consumption behavior is one of the key reasons that affects hotel buildings’ energy consumption. However, there has been little research study that provides efficient energy-use reduction interventions based on guests’ energy-related behavior in hotel buildings. To address this research gap, this research study aims to develop an integrated energy-use framework in four steps: (1) integrating four energy-related behavior models (i.e., Motivation-Opportunity-Ability, Norm Activation Model, Theory of Planned Behavior, and Pro-environmental Behavior); (2) developing a set of hypotheses and their relevant measures to examine the relationship between the energy-related behavior models and hotel guests’ energy-use behavior; (3) conducting an energy-use survey to analyze the effect of each determined measure on hotel guests’ energy-use behavior; (4) analyzing the energy behavior data to identify energy-use behavior of hotel guests in hotel buildings; (5) analyzing the energy behavior data to identify energy-use profiles (i.e., Prone, Indifferent, or Resistant to Change) of hotel guests in hotel buildings. In this study, Prone to Change refers to good energy consumption behavior, Indifferent to Change refers to moderate energy consumption behavior, and Resistant to Change refers to bad or dark energy consumption behavior. From the energy-use survey, 370 responses were collected. Then, the 370 responses were analyzed to identify the energy-use profiles of hotel guests. The results from the analysis indicated that 168 out of 370 (45%) respondents have Resistant to Change energy-use profile, 146 out of 370 (40%) respondents have Indifferent to Change energy-use profile, and 56 out of 370 (15%) respondents have Prone to Change energy-use profile. The findings can provide decision-makers in hospitality industry with a better understanding of their guests’ energy-related behavior; and accordingly develop effective interventions to reduce energy consumption in hotel buildings.